2022
DOI: 10.1101/2022.06.26.22276840
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Omega-3 supplements in the prevention and treatment of youth depression and anxiety: A scoping review

Abstract: Introduction: Emerging evidence suggests that omega-3 supplements may be efficacious in reducing symptoms of depression and anxiety in adults, particularly as an adjunct to antidepressant medication. However, research on its efficacy in young people is limited. Thus, this scoping review aimed to summarise existing evidence on the efficacy of omega-3 supplementation in treating depression and anxiety in young people aged 14-24. Method: Four databases (Cochrane CENTRAL, EmBASE, PsycINFO and PubMed) were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…An analysis of 26,656 participants in the National Health and Nutrition Examination Survey (NHANES) revealed that depression occurred less in individuals who consumed walnuts compared with non-nut consumers, with this effect being strongest in women [15]. However, a scoping review recently concluded that omega-3 consumption in individuals aged 14-24 could not improve symptoms of anxiety and depression [41]. Parilli-Moser et al [42] showed in their randomised controlled trial that peanut consumption for 6 months could lower measures of depression and anxiety in young adults, and this was attributed to polyphenols present in peanuts altering faecal short-chain fatty acid levels.…”
Section: Questionnairesmentioning
confidence: 99%
“…An analysis of 26,656 participants in the National Health and Nutrition Examination Survey (NHANES) revealed that depression occurred less in individuals who consumed walnuts compared with non-nut consumers, with this effect being strongest in women [15]. However, a scoping review recently concluded that omega-3 consumption in individuals aged 14-24 could not improve symptoms of anxiety and depression [41]. Parilli-Moser et al [42] showed in their randomised controlled trial that peanut consumption for 6 months could lower measures of depression and anxiety in young adults, and this was attributed to polyphenols present in peanuts altering faecal short-chain fatty acid levels.…”
Section: Questionnairesmentioning
confidence: 99%